Ethno-Political Tkansformation in the States of the Former USSR - Juška, Arūnas (Sociologija. Mintis ir veiksmas, 1999)
The collapse of the USSR resulted in a decline of institutions which had supported the dominance of ethnic Russians throughout the periphery of the country. In their place new institutions and mechanisms have been developed to regulate the access of people of different nationalities to power, resources and prestige. This paper provides a comparative analysis of ethnic transformation in 10 of the 14 successor states of the former Soviet Union. The analysis identified five types of ethnic transformation in the successor states. In the Baltics the attempts of titular ethnic groups to secure predominance over ethnic Russians and radically transform institutions of the Soviet state resulted in the creation of exclusive ethnic democracies. In Central Asia an elite-negotiated transformation led to t h e emergence of ethnocracies in Turkmenistan, Tajikistan and Uzbekistan, while the regimes formed in Kazakhstan and Kyrgyzstan were characterized by a mixture of ethnocratic and consociationalist features. In Moldova a failed attempt at unification with Romania eventuated in policies directed toward the creation of a Moldovan ethno-territorial federation. Finally, in Ukraine gradual reforms and attempts to abolish any ethnic hierarchy have led to the creation of consociationalism, in which ethnic Russians and Ukrainians, Russophones and Ukrainophones share power over the state.